A guide to the European forage databases - European Cooperative Programme for Plant Genetic Resources (1991)
Members at the 3rd meeting of the European Cooperative Programme on Crop Genetic Resources Networks (ECP/GR) Forage Working Group in January 1989 reviewed the progress of institutes acting as European forage databases and decided that sufficient progress had been made to warrant publication of a booklet containing details of the programme and its databases for the benefit of a wider audience. This, the resulting publication, contains details in its first part of the ECP/GR programme, the Forage Working Group, standardized content and sorting order of the databases, and deviations to standardized contents. The second and main part of the booklet provides data for the individual databases, with details of curators, database content and availability, computer software and catalogues, plus tabulated data on the accessions documented. These databases are for Bromus (at Tapioszele, Hungary), Dactylis and Festuca (at Radzikow, Poland), Lathyrus (at Pau, France), Lolium perenne, L. multiflorum and Trifolium repens (at Aberystwyth, UK), annual Medicago spp. and T. subterraneum (at Badajoz, Spain), perennial Medicago spp. (at Lusignan, France), Phleum (at Alnarp, Sweden), Poa (at Braunschweig, Germany) and T. pratense (at Nyon, Switzerland). An annex provides definitions of the descriptors used. (Abstract © CAB ABSTRACTS, CAB International)